Understanding Exchange Rates: A Weakening U.S. Dollar--Good, Bad, or Indifferent for Florida Farmers and Agribusinesses? - Edward A. Evans (EDIS)
This publication explains the concept of fluctuating currency exchange rates, defines common terms used (such as strengthening or weakening of the dollar), discusses factors that determine the exchange rate, considers the potential implications of a weak U.S. dollar on U.S. and South Florida agriculture in general, and makes a few suggestions regarding what farmers and agribusinesses can do to protect themselves from currency fluctuations. This is EDIS document FE546, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published April 2005.